Analysis of the results adequacy of the fuselage finite-element modeling in the vicinity of a large cutout - A. V. Boldyrev; M. V. Pavelchuk (Научный вестник МГТУ ГА)
The issues of ensuring the reliability of the finite element models (FEM) of the fuselage in the hatch cutout zone are considered at the early aircraft design stages. The purpose and tasks of research are formulated. To assess the reliability of mathematical models, the objects with standards were selected. The methods of experimental research and measuring instruments are discussed. The results of a comparative analysis of the numerical experiment with analytical solutions and full-size experiments data are presented. For the validation of FEM structures, the checkable characteristics and types of their verification are determined. The results of this research contain a discussion of the impact of finite element mesh details on a stress concentration factor, an adequacy of modeling the stress and strain field in the vicinity of the cutout and taking into account a nonlinearity in strength calculations of structures with stress concentration. This paper focuses on the analysis of modeling a framed cylindrical shell with a large rectangular cutout, for which full-size tests were conducted by TSAGI researchers. Strains of strong frames, limiting the cutout in a cylindrical shell, shearing and equivalent stress in the skin, normal stresses in stringers at the intersection with the strong frame, displacements of strong frames cross-sections at test points are analyzed. Based on the results of this research, the recommendations for modeling thin-walled fuselage structures in the vicinity of a large cutout, ensuring the performance of calculations with engineering accuracy were formulated.